First checklist of the ants (Hymenoptera: Formicidae) of French Guiana - Franco, Weslly; Ladino, Natalia; Delabie, Jacques H. C.; Dejean, Alain; Orivel, Jerôme; Fichaux, Mélanie; Groc, Sarah; Leponce, Maurice; Feitosa, Rodrigo M. (Zootaxa, 2019)
We provide here a checklist of the ants of French Guiana, an overseas department of France situated in northern South America, with a very low human population density and predominantly covered by old-growth tropical rainforests. Based on 165 scientific papers, specimens deposited in collections, and unpublished surveys, a total of 659 valid species and subspecies from 84 genera and 12 subfamilies is presented. Although far from complete, these numbers represent approximately 10% of the ant diversity known to occur in the Neotropical realm. Additionally, three ant genera and 119 species are reported for the first time for French Guiana. Finally, five species are recognized as erroneous records for the the department in the literature. This checklist significantly expands the basic knowledge of the ants in the Guiana Shield, one of the world’s most important biodiversity hotspots.